MARRIAGE AND FAMILY TODAY: AN INDIAN THEOLOGICAL SEARCH - Mulackal, Shalini (Asian Horizons, 2015)
We, the members of the Indian Theological Association (ITA) assembled at ANUGRAHA Renewal Centre, Vazhoor, Kottayam, on the occasion of the 38th Annual Meeting cum Conference, from 30 April to 3 May 2015, to reflect and deliberate on the theme “Marriage and Family Today – An Indian Theological Search” and propose new pastoral approaches to meet the contemporary challenges. We express our conviction that the whole Church in India needs to revisit the current theology of marriage and family and create a new praxis of pastoral care in the light of a liberative reading of the Word of God, the signs of the times and in the context of the Synod of Bishops on Family.